Diagnostic accuracy of haemophilia early arthropathy detection with ultrasound (HEAD-US) - Plut, Domen (Radiology and oncology (Ljubljana), 2019)
Background. Repeated haemarthroses affect approximately 90% of patients with severe haemophilia and lead to progressive arthropathy, which is the main cause of morbidity in these patients. Diagnostic imaging can detect even subclinical arthropathy changes and may impact prophylactic treatment. Magnetic resonance imagining (MRI) is generally the gold standard tool for precise evaluation of joints, but it is not easily feasible in regular follow-up of patients with haemophilia. The development of the standardized ultrasound (US) protocol for detection of early changes in haemophilic arthropathy (HEAD-US) opened new perspectives in the use of US in management of these patients. The HEAD-US protocol enables quick evaluation of the six mostly affected joints in a single study. The aim of this prospective study was to determine the diagnostic accuracy of the HEAD-US protocol for the detection and quantification of haemophilic arthropathy in comparison to the MRI. Patients and methods. The study included 30 patients with severe haemophilia. We evaluated their elbows, ankles and knees (overall 168 joints) by US using the HEAD-US protocol and compared the results with the MRI using the International Prophylaxis Study Group (IPSG) MRI score. Results. The results showed that the overall HEAD-US score correlated very highly with the overall IPSG MRI score (r = 0.92). Correlation was very high for the evaluation of the elbows and knees (r - 0.95), and slightly lower for the ankles (r - 0.85). Conclusions. HEAD-US protocol proved to be a quick, reliable and accurate method for the detection and quantification of haemophilic arthropathy.
Keywords: haemophilia; haemophilic arthropathy; hemofilija; hemofilno artropatijo; magnetic resonance imaging; slikanje z magnetno resonanco